Integration of geophysical methods in the study of acid drainage in uranium mining waste - Casagrande, Matheus Felipe Stanfoca [UNESP]; Moreira, César Augusto [UNESP]; Targa, Débora Andrade [UNESP]; Alberti, Heber Luiz Caponi (My University, 2018)
Among the potential environmental impacts in mining activities, acid mine drainage (AMD) is a relevant problem caused by reactive minerals, such as sulfides, due to their exposure to the surface conditions. This is the context of contamination of a waste pile (BF-04) at Osamu Utsumi mine, closed in 1995 after years of physical and chemical processing of the uranium ore and currently under decommissioning plan. This study is based on the application of the combined geophysical methods of Electrical Resistivity and Induced Polarization and the analysis of previous geochemical data, aiming the evaluation of zones related to the generation of AMD and groundwater flux into the waste pile BF-04, containing sulfide minerals and uranium. The association of high resistivity and high chargeability zones is related to disseminated sulfide minerals in rock with silica cement. Infiltration of meteoric water through those zones induces the oxidation of sulfides, high sulfur concentration in groundwater followed by a drop in pH values, which results in a higher leaching capacity and solubility of ions and heavy metals. In addition, high chargeability zones (higher than 10 mV/V) represent portions of generation of AMD, while the low resistivity anomalies (under 70 W:m) are related to preferential flow zones of the contaminated groundwater.
Keywords: Chargeability; Electrical resistivity; Minning; Sulfides; Uranium